Strategi Perancangan Infografik di Layanan Jejaring Sosial Instagram dalam Perspektif Desainer. Designer's perspective on the Strategy of Designing Infographics on Social Network Services (SNS): Instagram - Muhammad Harun Rosyid Ridlo (Graduate School of the Indonesia Institute of the Arts Yogyakarta, 2020)
Penerbitan infografik di Instagram memiliki tantangan berat. Infografik di Instagram harus berhadapan dengan berbagai jenis terbitan dan keberagaman motivasi pengguna. Tujuan kajian ini adalah untuk mengeksplorasi berbagai strategi perancangan infografik di Instagram. Responden dalam penelitian ini adalah sebanyak 32 perancang yang ditanya melalui angket daring. Seluruh data dianalisis berdasarkan hubungan antara kualitas dan strategi perancangan infografik. Hasilnya, ada beberapa strategi yang dilakukan para perancang: kesegaran dan urgensi topik, tampilan yang atraktif dan kejelasan informasi, resonansi terhadap emosi dan memori, serta validitas informasi.Infographics posting on Instagram faces some major challenges. It needs to deal with the various types of posts and the diverse motivations of the users. Hence, this study aims to explore various strategies of infographics design on Instagram. The total respondents are 32 designers who have answered an online questionnaire. Meanwhile, the collected data were analyzed based on the relation between the infographics design quality and strategy. The result shows that there are several strategies implemented by the designers, those are; immediacy and urgency of the topics, attractive displays and information clarity, resonance with emotion and memories, and information validity.